Intrinsic Auricular Muscle Zone Stimulation Improves Walking Parameters of Parkinson's Patients Faster Than Levodopa in the Motion Capture Analysis: A Pilot Study - Cakmak, Yusuf O.; Ozsoy, Burak; Ertan, Sibel; Cakmak, Ozgur O.; Kiziltan, Gunes; Yapici-Eser, Hale; Ozyaprak, Ecem; Olcer, Selim; Urey, Hakan; Gursoy-Ozdemir, Yasemin (Frontiers in Neurology, 2020)
It has been demonstrated that intrinsic auricular muscles zone stimulation (IAMZS) can improve the motor symptoms of Parkinson's disease (PD) patients who are examined with the Unified Parkinson's Disease Rating Scale (UPDRS) motor scores. In the present pilot study, using motion capture technology, we aimed to investigate the efficacy of IAMZS compared to medication alone or in combination with medication. Ten PD patients (mean age: 54.8±10.1 years) were enrolled. Each participant participated in three different sessions: sole medication, sole stimulation-20 minutes of IAMZS, and combined IAMZS (20 minutes) and medication. Each session was performed on different days but at the same time to be aligned with patients' drug intake. Motion capture recording sessions took place at baseline, 20, 40, and 60 min. Statistical analysis was conducted using one-way repeated measures ANOVA. Bonferroni correction was implemented for pairwise comparisons. The sole medication was ineffective to improve gait-related parameters of stride length, stride velocity, stance, swing, and turning speed. In the sole-stimulation group, pace-related gait parameters were significantly increased at 20 and 40 min. These improvements were observed in stride length at 20 (p=0.0498) and 40 (p=0.03) min, and also in the normalized stride velocity at 40 min (p-value=0.02). Stride velocity also tended to be significant at 20 min (p=0.06) in the sole-stimulation group. Combined IAMZS and medication demonstrated significant improvements in all the time segments for pace-related gait parameters (stride length: 20 min [p=0.04], 40 min [p=0.01], and 60 min [p<0.01]; stride velocity: 20 min [p<0.01], 40 min [p=0.01], and 60 min [p<0.01]). These findings demonstrated the fast action of the IAMZS on PD motor symptoms. Moreover, following the termination of IAMZS, a prolonged improvement in symptoms was observed at 40 min. The combined use of IAMZS with medication showed the most profound improvements. The IAMZS may be particularly useful during medication off periods and may also postpone the long-term side effects of high-dose levodopa. A large scale multicentric trial is required to validate the results obtained from this pilot study.